APPLICATION OF DIGITAL IMAGE CORRELATION METHOD IN MATERIALS - TESTING AND MEASUREMENTS: A REVIEW - ZAYA, MERNA ALEC; ADAM , SARHAT M.; ABDULRAHMAN, FARSAT HEETO (Journal of Duhok University, 2023)
Digital image correlation (DIC) is a non-contact optical approach that employs tracking and image registration techniques to evaluate image alterations within two or three dimensions precisely. The DIC approach's primary focus revolves around identifying similarities between images that have undergone deformation, commonly referred to as the "degraded image," and images that have remained unchanged, known as the "Reference image." This approach is utilized in diverse scientific and technical disciplines to measure full-field displacement and strains. DIC is widely recognized as a valuable and efficient technique for quantifying in-plane deformation. Moreover, DIC is currently being utilized to monitor the behavior of concrete before fractures, including the propagation and displacement of cracks. Additionally, new applications of DIC are continuously being discovered. This paper aims to review the various applications of DIC and compare its capabilities with conventional measurement techniques, such as gauges and transducers, in the context of material testing and deformation measurement